2013
DOI: 10.2527/jas.2012-5896
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of lateral saphenous vein serotonin receptors from steers grazing endophyte-free, wild-type, or novel endophyte-infected tall fescue1,2

Abstract: Pharmacologic profiling of serotonin (5HT) receptors of bovine lateral saphenous vein has shown that cattle grazing endophyte-infected (Neotyphodium coenophialum) tall fescue (Lolium arundinaceum) have altered responses to ergovaline, 5HT, 5HT2A, and 5HT7 agonists. To determine if 5HT receptor activity of tall fescue alkaloids is affected by grazing endophyte-free (EF), wild-type [Kentucky-31 (KY31)], novel endophyte AR542-infected (MAXQ), or novel endophyte AR584-infected (AR584) tall fescue, contractile resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 19 publications
3
38
0
Order By: Relevance
“…Specifically, this has been demonstrated using a bovine mesenteric artery and vein bioassay with both chronic ruminal dosing [8] and acute direct incubation [23] with ergovaline, which resulted in large decreases in vasoactivity after exposure. Prior work that evaluated the vasoactivity of the lateral saphenous vein in relation to cattle that had grazed toxic endophyte-infected or endophyte-free tall fescue demonstrated that veins from the toxic E+ were not as responsive [6,7]. Klotz et al [7] went on to demonstrate that vascular alterations induced by fescue toxicosis were ameliorated in steers following a 91 to 103 day finishing period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, this has been demonstrated using a bovine mesenteric artery and vein bioassay with both chronic ruminal dosing [8] and acute direct incubation [23] with ergovaline, which resulted in large decreases in vasoactivity after exposure. Prior work that evaluated the vasoactivity of the lateral saphenous vein in relation to cattle that had grazed toxic endophyte-infected or endophyte-free tall fescue demonstrated that veins from the toxic E+ were not as responsive [6,7]. Klotz et al [7] went on to demonstrate that vascular alterations induced by fescue toxicosis were ameliorated in steers following a 91 to 103 day finishing period.…”
Section: Discussionmentioning
confidence: 99%
“…As was hypothesized in the current study, contractile responses of lateral saphenous veins biopsied from tall fescue steers were much lower compared to those of control steers that had previously grazed bermudagrass pasture on 0 day off pasture. Chronic alkaloid exposure over time affects the function of adrenergic and serotonergic receptors [6,7,33]. Once the steers were removed from E+ tall fescue pastures, dissipation of ergot alkaloids from cellular binding sites on receptors or a gradual turnover of alkaloid-receptor complexes may lead to increased contractility of vascular tissues as seen on Day 63 with saphenous veins from tall fescue steers exhibiting contractile responses similar to those of bermudagrass steers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important for the researcher to understand the flexibility of the treatment structure applied to this bioassay. A researcher can add any compound to the incubation buffer that he or she is interested in chronically exposing the blood vessels to in order to control something of biologic relevance or as a treatment (in the case of Klotz et al 17 , this was done with lateral saphenous veins continuously exposed to ketanserin, which antagonized a serotonin receptor of interest). The mesenteric blood vessels could be pretreated with a compound of interest prior to conducting a contractile response experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Klotz et al (2012) further defined serotonergic receptor involvement by reporting that lateral saphenous vein responses to 5HT2A and 5HT7 agonists were altered in cattle that grazed endophyteinfected tall fescue. Using this same bovine bioassay, Klotz et al (2013) found that antagonism of the 5HT2A receptor not only suppresses the contractile responses of ergovaline, ergotamine and ergocornine, but that cattle that had grazed endophyte-infected tall fescue pastures were more sensitive to lower concentrations of these compounds.…”
Section: Serotonergic Receptor Involvementmentioning
confidence: 93%